Clinical Challenges with Talimogene Laherparepvec: Cured Lymph Nodes Masquerading as Active Melanoma. (7th March 2019) - Swami, Umang; Swick, Brian; Zakharia, Yousef; Milhem, Mohammed
Abstract : Talimogene laherparepvec is a novel, genetically engineered, oncolytic herpes virus approved for local treatment of unresectable cutaneous, subcutaneous, and nodal lesions in patients with melanoma recurrent after initial surgery. It is administered as an intralesional injection. However, if the lesion continues to persist, it presents with a clinical challenge as when to stop treatment. Herein, we present two cases from our institution wherein the disease appeared to be persistent radiologically; however, on pathological excision, there was no evidence of disease and patients continue to be in durable remission after stopping treatment.